Occupational noise exposure and risk of incident stroke: a pooled study of five Scandinavian cohorts. Issue 9 (21st April 2022) - Thacher, Jesse D; Roswall, Nina; Lissåker, Claudia; Aasvang, Gunn Marit; Albin, Maria; Andersson, Eva M; Engström, Gunnar; Eriksson, Charlotta; Hvidtfeldt, Ulla Arthur; Ketzel, Matthias; Khan, Jibran; Lanki, Timo; et al.
Abstract : Objectives: To investigate the association between occupational noise exposure and stroke incidence in a pooled study of five Scandinavian cohorts (NordSOUND). Methods: We pooled and harmonised data from five Scandinavian cohorts resulting in 78 389 participants. We obtained job data from national registries or questionnaires and recoded these to match a job-exposure matrix developed in Sweden, which specified the annual average daily noise exposure in five exposure classes (LAeq8h ): <70, 70–74, 75–79, 80–84, ≥85 dB(A). We identified residential address history and estimated 1-year average road traffic noise at baseline. Using national patient and mortality registers, we identified 7777 stroke cases with a median follow-up of 20.2 years. Analyses were conducted using Cox proportional hazards models adjusting for individual and area-level potential confounders. Results: Exposure to occupational noise at baseline was not associated with overall stroke in the fully adjusted models. For ischaemic stroke, occupational noise was associated with HRs (95% CI) of 1.08 (0.98 to 1.20), 1.09 (0.97 to 1.24) and 1.06 (0.92 to 1.21) in the 75–79, 80–84 and ≥85 dB(A) exposure groups, compared with <70 dB(A), respectively. In subanalyses using time-varying occupational noise exposure, we observed an indication of higher stroke risk among the most exposed (≥85 dB(A)), particularly when restricting analyses to people exposed to occupational noise within the last year (HR: 1.27; 95% CI: 0.99 to 1.63). Conclusions: We found no association between occupational noise and risk of overall stroke after adjustment for confounders. However, the non-significantly increased risk of ischaemic stroke warrants further investigation.